2018
DOI: 10.3389/fpsyt.2018.00454
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Intrarectal Administration of Sodium Propionate Induces Antidepressant-Like Effects in Rats Exposed to Chronic Unpredictable Mild Stress

Abstract: Depression has been correlated with metabolic disorders, and the gut microbiota and its metabolites have been reported to be key factors affecting metabolic disorders. Several metabolites generated by the gut microbiota have been reported to exert antidepressant-like effects, including the short chain fatty acid (SCFA) butyrate. However, recent work has suggested that the abundance of butyrate is not significantly changed in neither human nor experimental animals with depression, and butyrate has been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The SCFA propionate also acts as a HDAC inhibitor [104], and intrarectal administration of sodium propionate was shown to improve despair behavior in rats [105]. The antidepressant effect of propionate was accompanied by an increase in norepinephrine, dopamine, tryptophan, 5-HIAA and 3-hydroxyanthranilic acid (3-HAA) in the prefrontal cortex, although no change was detected in 5-HT and 3-hydroxykynurenine (3-HK).…”
Section: Neuroactive Microbial Metabolites and Their Role In Depressionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SCFA propionate also acts as a HDAC inhibitor [104], and intrarectal administration of sodium propionate was shown to improve despair behavior in rats [105]. The antidepressant effect of propionate was accompanied by an increase in norepinephrine, dopamine, tryptophan, 5-HIAA and 3-hydroxyanthranilic acid (3-HAA) in the prefrontal cortex, although no change was detected in 5-HT and 3-hydroxykynurenine (3-HK).…”
Section: Neuroactive Microbial Metabolites and Their Role In Depressionmentioning
confidence: 99%
“…Both butyrate and propionate may also contribute to dopaminergic function by inhibiting the expression of dopamine-β-hydroxylase, which catalyzes the conversion of dopamine into norepinephrine. Thus, the opposite effects of SCFAs on behavior may be explained by their action via independent mechanisms: for example, Li et al [105] found that while butyrate modulated the expression of 5-HT (with slow-onset but long-term antidepressant action), propionate altered the expression of norepinephrine (with fast-acting, but short-term antidepressant action). However, propionate is also able to modulate serotonergic function by increasing the expression of tryptophan hydroxylase (TPH) [101], responsible for the conversion of tryptophan to 5-HT.…”
Section: Neuroactive Microbial Metabolites and Their Role In Depressionmentioning
confidence: 99%
See 3 more Smart Citations